Using Blockchain Technology and Wordnet Semantic Relations For the Land Registry System - Piotr POTIOPA; Rafał RUMIN; Agnieszka KUBIAK-CYRUL (Communications of International Proceedings, 2021)
The purpose of this paper is to present a prototype of an IT solution using two technologies, WordNet and Blockchain, to develop a new type of Land Registry tool. The present Electronic Land and Mortgage Register system in Poland is characterized by accessibility and transparency of information and constitutes an important dataset of information concerning the legal status of immovable property. The availability of this information via the Internet enables interested parties to verify the property before buying it and is an important factor in increasing the security of such transactions. However, there are situations in which information management system and the procedure for entering and updating entries in the land register, due to its architecture and the influence of human factors, can lead to errors or abuse. The development of DLT (Distributed Ledger Technology) provides an opportunity to use a distribiuted blockchain-based system for keeping the Land Register. It provides many additional benefits - automatically performed operations based on current entries in the register (so-called blockchain oracles) and automatically validated legal actions, e.g. sale, division or other changes in immovable property, with simultaneous protection against modification of previous entries etc. In addition, the introduction of an intelligent search system for the new blockchain-based Land Register, using methods for calculating semantic similarity of texts based on the use of WordNet, will enable a more intuitive interface linking the database to queries from its users.
Keywords: Land Registry; WordNet; Blockchain; Semantic Similarity.